The Golgi Apparatus May Be a Potential Therapeutic Target for Apoptosis-Related Neurological Diseases - He, Qiang; Liu, Hui; Deng, Shuwen; Chen, Xiqian; Li, Dong; Jiang, Xuan; Zeng, Wenbo; Lu, Wei (Frontiers in Cell and Developmental Biology, 2020)
Increasing evidence shows that in addition to the classical function of protein processing and transport, the Golgi apparatus is also involved in apoptosis, one of the most common forms of cell death. The structure and function of the Golgi apparatus is damaged during apoptosis. However, the specific effect of the Golgi apparatus on the apoptosis process is unclear; it may be involved in initiating or promoting apoptosis, or it may inhibit apoptosis. Golgi-related apoptosis is associated with a variety of neurological diseases including glioma, Alzheimer’s disease, Parkinson’s disease, and ischemic stroke. This review summarizes the changes and possible mechanisms of Golgi structure and function during apoptosis. In addition, we also explore the possible mechanisms by which the Golgi apparatus regulates apoptosis and summarize the potential relationship between the Golgi and certain neurological diseases from the perspective of apoptosis. Elucidation of the interaction between the Golgi apparatus and apoptosis broadens our understanding of the pathological mechanisms of neurological diseases and provides new research directions for the treatment of these diseases. Therefore, we propose that the Golgi apparatus may be a potential therapeutic target for apoptosis-related neurological diseases.